The Plasmodium falciparum Hsp70‐x chaperone assists the heat stress response of the malaria parasite. Issue 12 (14th November 2019) - Day, Jemma; Passecker, Armin; Beck, Hans‐Peter; Vakonakis, Ioannis
Abstract : Plasmodium falciparum is the most lethal of human‐infective malaria parasites. A hallmark of P. falciparum malaria is extensive remodeling of host erythrocytes by the parasite, which facilitates the development of virulence properties such as host cell adhesion to the endothelial lining of the microvasculature. Host remodeling is mediated by a large complement of parasite proteins exported to the erythrocyte; among them is a single heat shock protein (Hsp)70‐class protein chaperone, P. falciparum Hsp70‐x (PfHsp70‐x). PfHsp70‐x was previously shown to assist the development of virulent cytoadherence characteristics. Here, we show that PfHsp70‐x also supports parasite growth under elevated temperature conditions that simulate febrile episodes, especially at the beginning of the parasite life cycle when most of host cell remodeling takes place. Biochemical and biophysical analyses of PfHsp70‐x, including crystallographic structures of its catalytic domain and the J‐domain of its stimulatory Hsp40 cochaperone, suggest that PfHsp70‐x is highly similar to human Hsp70 chaperones endogenous to the erythrocyte. Nevertheless, our results indicate that selective inhibition of PfHsp70‐x function using small molecules may be possible and highlight specific sites of its catalytic domain as potentially of high interest. We discuss the likely roles of PfHsp70‐x and human chaperones in P. falciparum biology and how specific inhibitors may assist us in disentangling their relative contributions.—Day, J., Passecker, A., Beck, H.‐P., Vakonakis, I. The Plasmodium falciparum Hsp70‐x chaperone assists the heat stress response of the malaria parasite. FASEB J. 33, 14611‐14624 (2019). www.fasebj.org